The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.23887/ijssb.v4i4.30411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Employee Satisfaction Towards Salary, Position, Position Promotion, and Supervision

Abstract: Job satisfaction is a general attitude towards one's job, as the difference between the amount of reward received by workers and the amount of reward that is believed to be received. This research aims to analyze employee job satisfaction with salary, position, promotion, and supervision. This research is a quantitative study using a survey method. The population in this study were 70 people. The sample was obtained using a saturated sample technique. The data in this study were collected using a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…It is in harmony with the research findings reported by Zandi et al (2018) that precisely ascertained extrinsic job satisfaction is the main factor in determining the relation between job satisfaction and normative commitment. Adequate pay, salary, or fee are found to be the highest choice, as also discovered by Putra & Asnur (2020), Mohapatra, Satpathy &Patnaik (2019), andSaman (2020). Support and relations with co-workers significantly impact workers' job satisfaction (Abdelmoula, 2020) or organizational commitment (Nguyen et al, 2021).…”
Section: Indicator To Predict Job Satisfactionmentioning
confidence: 97%
“…It is in harmony with the research findings reported by Zandi et al (2018) that precisely ascertained extrinsic job satisfaction is the main factor in determining the relation between job satisfaction and normative commitment. Adequate pay, salary, or fee are found to be the highest choice, as also discovered by Putra & Asnur (2020), Mohapatra, Satpathy &Patnaik (2019), andSaman (2020). Support and relations with co-workers significantly impact workers' job satisfaction (Abdelmoula, 2020) or organizational commitment (Nguyen et al, 2021).…”
Section: Indicator To Predict Job Satisfactionmentioning
confidence: 97%
“…Gaji, promosi kerja, dan supervisi atasan menjadi indikator kepuasan kerja perawat. (Putra & Asnur, 2020).…”
Section: Pendahuluanunclassified
“…With job satisfaction, work can be finished more quickly, damage can be lessened, attendance can be lower, employee movements can be reduced, work productivity can rise, and unit costs can be lower [43]. The indicators used to measure job satisfaction are pay, promotion, coworkers, nature of work, and supervision [44]- [46]. The extent to which technical assistance, attention, and encouragement are shown by the closest supervisor to the subordinates.…”
Section: Introductionmentioning
confidence: 99%